2007
DOI: 10.1007/s10745-007-9143-4
|View full text |Cite
|
Sign up to set email alerts
|

Securing Access to Seed: Social Relations and Sorghum Seed Exchange in Eastern Ethiopia

Abstract: Access to seed is crucial for farming, though few studies investigate household-level access in the informal 'farmer seed systems' which still supply most seed in poor countries. This paper uses empirical data of seed exchange practices for sorghum in eastern Ethiopia to analyze how social relationships influence access to off-farm seed for a major crop. Seed shortfalls are common, and farmer-farmer exchange is important for providing locally-adapted seed to fill this gap, but access varies considerably among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 30 publications
6
67
1
1
Order By: Relevance
“…The distribution of seed acquisition events across the main categories of social relationships over the two cropping seasons indicates that all farmers do not have the same ability to mobilize these emergency partners and to cope with climate unpredictability (Louette et al 1997, McGuire 2008. This result is supported by our ethnographic fieldwork, during which we observed that farmers belonging to households of the intermediate wealth stratum (generally young couples) were often those who were the most assisted.…”
Section: Social Inequalities In Facing Climatic Shocksmentioning
confidence: 51%
See 1 more Smart Citation
“…The distribution of seed acquisition events across the main categories of social relationships over the two cropping seasons indicates that all farmers do not have the same ability to mobilize these emergency partners and to cope with climate unpredictability (Louette et al 1997, McGuire 2008. This result is supported by our ethnographic fieldwork, during which we observed that farmers belonging to households of the intermediate wealth stratum (generally young couples) were often those who were the most assisted.…”
Section: Social Inequalities In Facing Climatic Shocksmentioning
confidence: 51%
“…Because of the patrilocal system, mothers and daughters can live in distant locations. In contrast, neighbors were not more frequently sought out in times of distress, but they represent a constant and basic source for all daily life exchanges (McGuire 2008).…”
Section: Cereal Substitution and Resilience Of The Networkmentioning
confidence: 99%
“…Other quantitative studies report comparable conclusions: in Malawi, Uganda, Ethiopia, Burundi, Ethiopia-the very poor are tied relatively more to local markets for seed of select crops than their wealthier neighbors (David and Sperling 1999;McGuire 2008;Sperling 1994). Future research will explore further the relationships between wealth (and farm area) and seed source use.…”
Section: Who Uses Specific Channels With Focus On Local Marketsmentioning
confidence: 86%
“…Empirically, where do farmers get the planting materials they sow, season after season, for which crops, where, on what scale? Multiple descriptions of seed system use do exist in the refereed and particularly grey literature -especially from anthropologists and agricultural economists (Badstue 2006;McGuire 2008;Nagarajan et al 2007). Existing studies tend to be of two types 3 : those that focus on intensive single crop analyses and often at a single site (e.g., Christinck 2002) or relatively sweeping regional and national analyses, which look at broad household socio-economic parameters and give insight on what might be happening in select seed-related domains (e.g., Nordhagen and Pascual 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, customers could select disease-free planting material (Gibson et al 2000), had the benefit of judging the quality of the planting material and, by purchasing, ensured the system is sustained year after year. Bartering and mutual aid still occurred but, as with most crops (McGuire 2008), selling was the norm. A multiplier commonly supplied 1-2 bundles of vines to each of ~50 customers in 2013.…”
Section: Discussionmentioning
confidence: 99%